A retrospective study of medical emergency management in a Health Center in Greece - Kampouridou, Georgia; Arkouda, Amalia; Toylia, Georgia; Gerogianni, Georgia; Marvaki, Christina (Health & Research Journal, 2021)
Ιntroduction: Primary Health Centers face a plethora of emergencies of different nature and severity and it is necessary a decision -whether or not to refer patients to the nearest hospital for further treatment and investigation- to be made. Aim: The aim of the present study was to investigate the management of emergencies in a HC of regional type near a large urban center. Material and Methods: This was a retrospective study. The data of 400 randomly selected patients admitted to the health center with acute conditions during the years 2017-2018 were recorded. Results: Out of all cases examined, 22% were rated as truly medical emergencies and 44% as not; 34% were classified as urgent; 25.9% of patients had arrived within the first hour of onset of symptoms, while 81.7% had already reached within the first 24 hours. Pain and respiratory diseases were the most common problems. In 15% of cases the patient was ambulance-transported to hospital. The proportion of ambulance referral to the nearest hospital was higher in patients with comorbidities (18.8%) than in those without (14.9%); 76% of cases were treated in accordance with evidence-based practice. Conclusions: Despite the significant progress made in treating patients in the community, it is necessary to improve management of non-emergency cases, as well as to improve the procedures for emergencies management in the HCs.